Fluid overload and mortality in critically ill patients with severe heart failure and cardiogenic shock–An observational cohort study - Waskowski, Jan; Michel, Matthias C.; Steffen, Richard; Messmer, Anna S.; Pfortmueller, Carmen A. (Frontiers in Medicine, 2022)
Objective: Patients with heart failure (HF) and cardiogenic shock are especially prone to the negative effects of fluid overload (FO), however fluid resuscitation in respective patients is sometimes necessary resulting in FO. We aimed to study the association of FO at ICU discharge with 30-day mortality in patients admitted to the ICU due to severe heart failure and/or cardiogenic shock. Methods: Retrospective, single center cohort study. Patients with admission diagnoses of severe HF and/or cardiogenic shock were eligible. Following exclusion criteria applied: I) patients younger than 16 years, II) patients admitted to our intermediate care unit, III) patients with incomplete data to determine FO at ICU discharge. We used a cumulative weight adjusted definition of fluid balance and defined more than 5% as FO. Data was analysed by univariate and adjusted univariate logistic regression. Results: We included 2158 patients in our analysis. 185 patients (8.6%) were fluid overloaded at ICU discharge. Mean FO in the FO-group was 7.2% (Interquartile range [IQR] 5.8%-10%). In patients with FO at ICU discharge, 30-day mortality was 22.7% compared to 11.7% in non-FO patients (p<0.001). In adjusted univariate logistic regression, we did not observe any association of FO at discharge with 30-day mortality (Odds ratio [OR] 1.48; 95% confidence interval [CI] 0.81 – 2.71, p=0.2). No association between FO and 30-day mortality was found in the subgroups with HF only or cardiogenic shock (all p>0.05). Baseline lactate (adjusted OR 1.27; 95%CI 1.13 - 1.42; p<0.001) and cardiac surgery at admission (adjusted OR 1.94; 95%CI 1.0 -3.76; p=0.05) were the main associated factors with FO at ICU discharge. Conclusion: In patients admitted to the ICU due to severe HF and/or cardiogenic shock, FO at ICU discharge seem not to be associated with 30-day mortality.